Penerapan Problem Based Learning (PBL) untuk Meningkatkan Hasil Belajar Materi Menghindari Perilaku Tercela pada Siswa Kelas XI MA Darul Amanah - naili, Naili Faizatur Rohmah; Mustafidin, Ahmad; Maskur; Panuntun, Slamet; Choirudin, Moch (Lembaga Penelitian dan Pengabdian Masyarakat STAI Brebes, 2025)
Based on the results of the daily assessment in the subject of Akidah Akhlak for Grade XI students at MA Darul Amanah Bedono in the even semester of the 2024/2025 academic year, only 2 out of 7 students (28.57%) achieved scores above the Minimum Mastery Criteria (KKM), while 5 students (71.43%) still received low scores. This outcome indicates that the learning process has not been effective and has not met the expected minimum competency targets. Furthermore, the low learning outcomes are also reflected in student behavior at school, which still shows a lack of application of commendable morals, such as insufficient respect for teachers, low concern for peers, and lack of participation in religious activities. This suggests that students' understanding of Akidah Akhlak is not only weak cognitively but is also not reflected in their daily attitudes and behavior.This study aims to improve student learning outcomes in the subject of Akidah Akhlak with the material